2019
DOI: 10.35407/bag.2019.xxx.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Taking Advantage of Organelle Genomes in Plant Breeding: An Integrated Approach

Abstract: Plant cells carry their genetic information in three compartments: the nucleus, the plastids and the mitochondria. In last years, next-generation sequencing has allowed the development of genomic databases, which are increasingly improving our knowledge about the role of nuclear and cytoplasmic genes as well as their interactions in plant development. However, most plant breeding efforts consider the utilization of the nuclear genome, while less attention is given to plastid and mitochondrial genomes. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 193 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Among 85 measured genes (31 in the chloroplast and 54 in the nucleus), 71 were affected by the nitrogen supply. Surprisingly, while all the 48 nuclear genes concerned were repressed in starvation, most of the cp genes (19) were upregulated: the transcriptional response of plastid genes seemed to be disconnected from that of nuclear genes under N starvation. Similar contrasted responses to N starvation have been reported for cp and nuclear genes for PSII and PSI in Chlamydomonas (Chlamydomonas reinhardtii), where the reaction center core subunits (encoded by plastid genes psbA and psbB for PSII; psaA and psaB for PSI) are more stable than the peripheral proteins and LHCII antenna proteins under N starvation [75].…”
Section: Disruption Of Cyto-nuclear Coadaptation Perturbs the Adaptiomentioning
confidence: 92%
See 1 more Smart Citation
“…Among 85 measured genes (31 in the chloroplast and 54 in the nucleus), 71 were affected by the nitrogen supply. Surprisingly, while all the 48 nuclear genes concerned were repressed in starvation, most of the cp genes (19) were upregulated: the transcriptional response of plastid genes seemed to be disconnected from that of nuclear genes under N starvation. Similar contrasted responses to N starvation have been reported for cp and nuclear genes for PSII and PSI in Chlamydomonas (Chlamydomonas reinhardtii), where the reaction center core subunits (encoded by plastid genes psbA and psbB for PSII; psaA and psaB for PSI) are more stable than the peripheral proteins and LHCII antenna proteins under N starvation [75].…”
Section: Disruption Of Cyto-nuclear Coadaptation Perturbs the Adaptiomentioning
confidence: 92%
“…In recent years, functional links between organellar retrograde signaling and plant response to environmental stresses have been substantially documented [16][17][18]. In parallel, many studies reported the role of organellar genetic variants in plant adaptation and crop performance [19,20]. Both nuclear and organelle genes jointly participate to the expression of organellar genomes and the constitution of multiproteic complexes [21,22], while genes in each compartment evolve at different paces [23,24].…”
Section: Introductionmentioning
confidence: 99%